A copper-catalyzed arylation/nucleophilic addition/fragmentation/C–S bond formation cascade: synthesis of bis(arylthio)imines. Issue 4 (16th January 2017) - Guo, Wei-Si; Wang, Yuan-Chao; Dou, Qian; Wen, Li-Rong; Li, Ming
Abstract : A new arylation/nucleophilic addition/fragmentation/C–S bond formation cascade was developed using isothiocyanates and diaryliodonium salts. Abstract : A new tandem arylation/nucleophilic addition/fragmentation/C–S bond formation reaction involving diaryliodonium salts as electrophiles was developed with Cu(OTf)2 as the catalyst. A series of unexpected bis(arylthio)imine derivatives were generated in good yields. The reaction proceeds under mild conditions, and the bis(arylthio)imines are readily transformed to other useful products.